(untitled) (National Administration Journal, 2025)
Marketers are increasingly imbuing AI into their products. Doing so enhances the various forms of value they offer. However, it also creates externalities. This commentary briefly addresses some of the broad socio-environmental dangers that AI poses. Environmentally, AI impacts pertain to pollution; land, electricity, and water usage; as well as communal life. Socially, AI impacts pertain to information quality, reality perceptions, interpersonal relationships, and mental health. The technology also undermines people’s independence, agency, culture, and purpose. This commentary thus strives to raise awareness among marketers of the potential consequences that their AI-enabled products might have, and to stimulate discussion as to how these impacts might be preemptively curtailed. Doing so is especially important for developing regions like Latin America, where socio-environmental impacts tend to be exacerbated.